Learning strategies for study and entrepreneurial attitude in University students - Noteno Condori, Erika Mercedes (2020)
The main objective of the research was the main strategy that was related to the entrepreneurial attitude in nursing students of a public university in Lima. A substantive research work was carried out, under the hypothetical-deductive methodology, non-experimental, cross-sectional. The population was made up of 75 students to whom the survey technique was applied, for which a questionnaire with Likert responses with reagents was developed. The results were estimated by logistic regression, using Spearman's Rho coefficient. In the descriptive results it was observed that 79% of the students presented a low and medium level in the use of information retrieval strategies. The general conclusion was the information acquisition strategy is the one with the greatest weight on the entrepreneurial attitude in specific the direct and significant relationship of the acquisition, coding, information retrieval and processing support strategies for the study with the entrepreneurial attitude of the students.